Os avós e os netos: um encontro de diferentes tempos verbais - Silva, Camila Cuencas Funari Mendes e [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper’s goal is the understanding of relations between generations among grandparents and grandchildren over the modern society. Therefore, we have elected Children Literature, particularly stories that treat the themed relation of grandparents and grandchildren, as one of the most various forms of the importance of symbolic exchanges between generations. In this study, we have selected two directed published articles to the children audience: Menina Nina: duas razões para não chorar, from the author Ziraldo (2002) and A menina, o cofrinho e a vovó, from Cora Coralina (2009). We have adopted the psychoanalytic reading as reference for the analysis of selected stories, once that it excels for the individual psychic construction, on its own unconscious conception and its interaction with social and cultural means, which allow us to explore and reflect over the bounds left behind from other generations. During this study at first we discuss about the aging of the world’s population, that comes to nowadays with a percentage in ascension, and yet we reflect regarding the concept of old age. We elected grandparents as one of the representatives of aging in XXI century and, for the eminently age criteria, we pointed out its matter on fulfilling the symbolic and social role that this figures have on their family life. Searching for a link between grandparents and grandchildren, we have found into Children Literature the required input in order to explore this connection, with its own unique way of communication and reflex of various aspects of human subjectivity. Psychoanalytic concepts have shown us that the base for the study of symbolic dimensions of psyche and relations between grandparents and grandchildren generation. With a psychoanalytic point of view, we synthesize our study with analyses of the stories from Ziraldo (2002) and Cora Coralina (2009)...

Este trabalho tem como objetivo a compreensão das relações intergeracionais entre avós e netos na sociedade contemporânea. Para tanto, elegemos a Literatura Infantil, especialmente em obras que tratam a temática da relação entre avós e netos, como uma das diversas formas de manifestação da importância das trocas simbólicas exercidas entre gerações. Na presente pesquisa, selecionamos duas publicações direcionadas ao público infantil: Menina Nina: duas razões para não chorar, de autoria de Ziraldo (2002) e A menina, o cofrinho e a vovó, de Cora Coralina (2009). Adotamos a leitura psicanalítica como referencial para análise das obras selecionadas, uma vez que ela prima pela construção psíquica do indivíduo, sua concepção inconsciente e sua interação com o meio social e cultural, o que nos possibilita explorar e refletir sobre os vínculos tecidos entre gerações. No percurso da pesquisa, primeiramente discorremos sobre o envelhecimento da população mundial, que se apresenta na atualidade com um percentual em ascensão, e ainda refletimos sobre a atualidade do conceito de velhice. Elegemos os avós como um dos representantes do envelhecimento no século XXI e, para além do critério eminentemente etário, destacamos sua importância no exercício da função simbólica e do papel social que essas figuras têm na vida familiar. Buscando um elo entre avós e netos, encontramos na Literatura Infantil os subsídios necessários para examinar esta conexão, com sua maneira singular de comunicação e reflexão de diversos aspectos da subjetividade humana. Os conceitos psicanalíticos serviram-nos de base para o estudo das dimensões simbólicas do psiquismo e das relações intergeracionais entre avós e netos. Com a construção de um olhar psicanalítico, sintetizamos nosso trabalho com a análise das obras de Ziraldo (2002) e Cora Coralina (2009)...
Keywords: Psicanalise; Avos e netos; Literatura infantojuvenil